First-principles study of structural, elastic, electronic, transport properties, and dielectric breakdown of Cs2Te photocathode - Gaoxue Wang; Jinlin Zhang; Chengkun Huang; Dimitre A. Dimitrov; Anna Alexander; Evgenya I. Simakov (Scientific Reports)
Abstract The pursuit to operate photocathodes at high accelerating gradients to increase brightness of electron beams is gaining interests within the accelerator community, particularly for applications such as free electron lasers (FEL) and compact accelerators. Cesium telluride (Cs2Te) is a widely used photocathode material and it is presumed to offer resilience to higher gradients because of its wider band gap compared to other semiconductors. Despite its advantages, crucial material properties of Cs2Te remain largely unknown both in theory and experiments. In this study, we employ first-principles calculations to provide detailed structural, elastic, electronic and transport properties of Cs2Te. It is found that Cs2Te has an intrinsic mobility of 20 cm2/Vs for electrons and 2.0 cm2/Vs for holes at room temperature. The low mobility is primarily limited by the strong polar optical phonon scattering. Cs2Te also exhibits ultralow lattice thermal conductivity of 0.2 W/(m*K) at room temperature. Based on the energy gain/loss balance under external field and electron–phonon scattering, we predict that Cs2Te has a dielectric breakdown field in the range from ~ 60 to ~ 132 MV/m at room temperature dependent on the doping level of Cs2Te. Our results are crucial to advance the understanding of applicability of Cs2Te photocathodes for high-gradient operation.